2022
DOI: 10.3389/fmars.2022.841027
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation Drives Changes in the Population Connectivity of Queen Conch (Aliger gigas)

Abstract: The queen conch, Aliger gigas, is an endemic and iconic marine gastropod of the Wider Caribbean region that has been harvested for thousands of years. Conch are slow-moving and require contact to mate; overfishing has reduced populations in many areas compromising its rates of reproduction. Long-range dispersal and mixing between distinct populations occur in the queen conch’s early life history stages, when pelagic larvae are transported by oceanic currents. Genetic studies suggest that gene flow between popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Our estimated ecological connectivity reflects unique events of dispersal of early life stages between spawning and recruitment sites (Vaz et al. 2022), while genetic connectivity typically reveals exchanges occurring during multiple generations or evolutionary timescales, exchanges that might occur at different ontogenetic stages and, thus, are not directly related to spawning–recruitment patterns (Bryan‐Brown et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our estimated ecological connectivity reflects unique events of dispersal of early life stages between spawning and recruitment sites (Vaz et al. 2022), while genetic connectivity typically reveals exchanges occurring during multiple generations or evolutionary timescales, exchanges that might occur at different ontogenetic stages and, thus, are not directly related to spawning–recruitment patterns (Bryan‐Brown et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2022; Vaz et al. 2022), and our model configuration relies on assumptions regarding the local hydrography and Red Snapper life history. This is the first larval dispersal study in the gulf using this particular high‐resolution (~2 km horizontal resolution) hydrodynamic fields model (Le Hénaff and Kourafalou 2016), which has been validated with observations by multiple studies in the gulf (Le Hénaff and Kourafalou 2016; Androulidakis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Queen conches can produce valuable pearls, but these are extremely rare . 3 Genetic work suggests that queen conches do not form a single panmictic population in the greater Caribbean (Stoner and Appeldoorn 2022;Vaz et al 2022). For instance, Truelove et al (2017) reported finding several regionally isolated queen conch populations throughout the region.…”
Section: Fishery Backgroundmentioning
confidence: 99%
“…However, most reserves are disconnected from each other (Andrello et al, 2017), making the long‐term viability of these important tools dependent on continued conservation research to inform spatial planning. Queen conch ( Aliger gigas ; hereafter: “conch”) is a species in decline due to overharvest (Vaz et al, 2022), has limited adult dispersal (Doerr & Hill, 2013), and is dependent on larval transport to shape population structure (Truelove et al, 2017). Past studies demonstrated that a population of conch in the oldest marine reserve in the wider Caribbean, the Exuma Cays Land and Sea Park (ECLSP), is dying out from old age, likely because of inadequate larval supply (Kough et al, 2017; Stoner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%